Towards urban development in Swaziland - Whittington, G. (ERDKUNDE, 1970)
The idea of living in the city, which was extremely important in its consequences, was introduced in Africa by the white settlers, but urban developments in Swaziland have only recently taken place. To date, Swaziland has had neither extensive mining areas nor large, market-oriented agricultural areas and has therefore not had an efficient transport network. The first urban centers have developed here in a similar way to the neighboring Republic of South Africa. Originally they had rectangular floor plans and sharply delineated racial quarters. However, there have been recent changes here. There are six urban areas in total, two of which, namely Mbabane and Manzini, appear to be growing into a dominant role, while the others are showing signs of decline due to changes and the inadequacies of the transport network. The current state of Swaziland’s urban system suggests that the country has fulfilled the conditions laid down in Friedmann’s model for an economic boom.